2021
DOI: 10.3389/fmats.2021.674798
|View full text |Cite
|
Sign up to set email alerts
|

Designing Oxide Aerogels With Enhanced Sorptive and Degradative Activity for Acute Chemical Threats

Abstract: Oxide aerogels are pore–solid networks notable for their low density, large pore volume, and high surface area. This three-dimensional arrangement of pore and solid provides critical properties: the high surface area required to maximize the number of active sites and a through-connected porosity that plumbs reactants to the active interior. In decontamination applications where reactivity beyond adsorption is desired to degrade deleterious molecules, oxide aerogels offer multiple avenues to add oxidative powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 106 publications
(180 reference statements)
0
11
0
Order By: Relevance
“…Due to the complex and turbulent international situation in contemporary society, chemical warfare agents (CWAs) remain pose huge and acute threats to ecological environment, agriculture and human health despite being explicitly banned decades ago by the Organization for the Prohibition of Chemical Weapons. Recent incidents in Syria and Malaysia have attracted renewed interest in novel materials for rapidly neutralizing and degrading these deadly agents that exist in liquid and aerosol forms. To date, apart from the impermeable encapsulated protective barriers with built-in breathing apparatus for personnel protection, activated carbon and its modified compounds have been the most exclusively used sorbents in filters to prevent accidental inhalation of CWAs. , However, these carbon-based materials still suffer from poor sorption capacity, secondary pollution after saturation, and high-cost ultimate disposal, which limit their practical application in the long run. , Thus, it is imperative to develop multifunctional chemical protective materials not only with appealing adsorptive capability but with the ability to decompose lethal chemical toxins into less toxic or nontoxic ones.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the complex and turbulent international situation in contemporary society, chemical warfare agents (CWAs) remain pose huge and acute threats to ecological environment, agriculture and human health despite being explicitly banned decades ago by the Organization for the Prohibition of Chemical Weapons. Recent incidents in Syria and Malaysia have attracted renewed interest in novel materials for rapidly neutralizing and degrading these deadly agents that exist in liquid and aerosol forms. To date, apart from the impermeable encapsulated protective barriers with built-in breathing apparatus for personnel protection, activated carbon and its modified compounds have been the most exclusively used sorbents in filters to prevent accidental inhalation of CWAs. , However, these carbon-based materials still suffer from poor sorption capacity, secondary pollution after saturation, and high-cost ultimate disposal, which limit their practical application in the long run. , Thus, it is imperative to develop multifunctional chemical protective materials not only with appealing adsorptive capability but with the ability to decompose lethal chemical toxins into less toxic or nontoxic ones.…”
Section: Resultsmentioning
confidence: 99%
“…4−6 To date, apart from the impermeable encapsulated protective barriers with built-in breathing apparatus for personnel protection, activated carbon and its modified compounds have been the most exclusively used sorbents in filters to prevent accidental inhalation of CWAs. 7,8 However, these carbon-based materials still suffer from poor sorption capacity, secondary pollution after saturation, and high-cost ultimate disposal, which limit their practical application in the long run. 9,10 Thus, it is imperative to develop multifunctional chemical protective materials not only with appealing adsorptive capability but with the ability to decompose lethal chemical toxins into less toxic or nontoxic ones.…”
mentioning
confidence: 99%
“…For example, ASZM-TEDA-activated carbon impregnated with copper, silver, zinc, molybdenum, and triethylenediamine is used as a filter material in gas masks . Metal oxides are also considered as potential filter materials for protection against CWAs because of their versatile surface chemistry toward different molecules. However, the relatively low surface area of metal oxides in comparison with that of carbon-based materials implied that so far, there have been certain limitations on using them as filter materials.…”
Section: Introductionmentioning
confidence: 99%
“…The NOGA, which consists of high-quality non-oxidized graphene akes (NOGFs) assembled into a aligned vertical structure, was shown to signicantly enhance the OER properties of the embedded copper oxide based active material by providing continuous pathways for shuttling both electrons and reactants to and from active sites. [32][33][34] Furthermore, we previously demonstrated that non-covalent functionalization of the NOGFs with adsorbed organic molecules provides precise control over the surface functional group, effectively doping the NOGFs into the desired electric modulation without damaging the basal plane. 35,36 Therefore, before applying g-C 3 N 4 , the NOGA is ndoped or p-doped using polyvinylpyrrolidone (PVP) or pyrenebutyric acid (PBA), respectively, and its effect on the catalytic activity of g-C 3 N 4 is analyzed.…”
Section: Introductionmentioning
confidence: 99%